Regeneração natural da flora lenhosa em um remanescente de caatinga sob diferentes níveis de perturbação, no semiárido sergipano - Soares, Natalie da Mota (2012)
Study on the dynamic of the natural regeneration are of great scientific interest, for being essential in the correct elaboration of plans of management and sylvicultural treatment, allowing a rational and permanent use of forest resources. This way, the present work was realized with the goal of studying the natural regeneration in Conservation Unit from the semiarid of Sergipe, investigating the capacity of resilience of three Caatinga environments, under different levels of anthropic intervention. The work was realized in a remaining set located in the High Wilderness of Sergipe, belonging to the Conservation Unit Monumento Natural Grota do Angico (MONA) located in the latitude 09º39'36" South e longitude 37º47'22" West. Three areas were selected, based on the environmental zoning of the management planning of the MONA: the zone of Extensive Use (49.93 ha), considered a zone of medium level of degradation; and, at last, the Recovering Zone (83.82 ha), a very altered area of Caatinga, which must be hereafter recovered to reach a better state of conservation. To the realization of the natural regeneration analysis, were installed 15 parts of 2 x 20 m where were shown all the individuals of woody (living) species, with diameter to soil level (DSL) smaller than 3 cm and minimal height of 15 cm. The levies occurred in the months of January and May of 2012, where were collected data from each species: height and diameter of the individual. To the analysis of the structural aspects from the regenerative stratum, the levied individual were stratified in four size classes: Class 1 individuals with height varying between 0.15 m to 0.49 m; Class 2 individuals with height varying between 0.50 m to 1,49 m; Class 3 individuals with height varying between 1.50 m to 2.5 m and Class 4 individuals with height superior to 2.5 m. To characterize the structural aspects of natural regeneration, were obtained the values of density, frequency, and total natural regeneration by specie. To evaluate the floristic diversity of the three environments, were used the index of Shannon-Weaver (H ) and of equability from Pielou (J ). Were also realized two analysis: one to determine the degree of floristic similarity between the shown environments, through the comparison between them, using the similarity index of Jaccard; and other to verify the pattern of space distribution of the community species, using, to the calculus, the index of Payandeh. In the levy concerning floristic, 17 taxons were identified to the level of species, 2 in gender and 1 remained undetermined. Altogether, were sampled 333 individuals belonging to 14 botanic families, 19 genders and 20 species. Analyzing the studied areas, the families with greater abundance of species in the regenerative stratum were Fabaceae-Mimosoideae (4) and Fabaceae- Caesalpiniodeae (3), because together presented 31.3% and 33.3% of the species levied in the first and second inventories, respectively. The smallest numbers of relative abundance were registered to the species: Myracrodruon urundeuva Allemão, Schinopsis brasiliensis Engl., Mimosa tenuiflora (Willd.) Poir., Mimosa sp., Piptadenia stipulacea (Benth.) and Sp. (Undetermined). In a general way, the species in more advanced phase of the vegetative cycle (Classes III and IV) were few registered in all the survey, reaching only 19% of the sampled individuals in the three environments during the first evaluation. The species which presented greater values of absolute density throughout the xi sampling were: Commiphora leptophloeos (Mart.) J.B. Gillett, Poincianella pyramidalis (Tul.) L.P.Queiroz, Jatropha mollissima (Pohl) Baill. and Bauhinia cheilantha (Bong.) Steud.. The species which presented the greater indexes of natural regeneration (RNT%) were: Bauhinia cheilantha (50,6%), Jatropha mollissima (38.2%), Poincianella pyramidalis (29.1%) and Commiphora leptophloeos (27.5%) in the first inventory; and Poincianella pyramidalis (30.3%), Bauhinia cheilantha (29.0%) and Commiphora leptophloeos (23.5%) in the second inventory. Related to the diversity of Shannon-Weaver between the studied environments were observed the following values: H (Primitive Zone)= 1.21 nats individual-1; H (Recovering Zone) = 1.8 nats individual-1 and H (Extensive Use Zone) = 1.99, in the first evaluation; and H (Primitive Zone) = 1.35 nats individual-1; H (Recovering Zone) = 1.84 nats.individual-1 and H (Extensive Use Zone) = 1.75 nats individual-1, in the second evaluation. The diversity of the Extensive Use Zone was superior to the other environments in the first inventory and the Recovering Zone in the second. Although apparently variations have occurred, the analysis of variance (ANOVA) pointed that these values do not differ between themselves, determining a homogeneity between the diversity of species which occur in the three zones, as in the first, as in the second inventory. To the floristic similarity it was possible to receive the formation of two well defined groups, the first group with the parcels located in the Primitive Zone and Recovering Zone, and the second with the parcels in the Extensive Use Zone. The majority of the sampled species presented values superior to 1 to the index of space distribution of Payandeh, indicating that the most of them occurred attached to the space (50% of the species in the first levy and 62% of the species in the second levy). The levels of anthropic disturbing did not affect directly in the process of natural regeneration and the area of study, in general, it still possess great potential of resilience, being able to unchain the process of natural regeneration, which is already in initial phase.